The role of citizenship in the acceptance and completion of COVID- 19 vaccine cycle in the resident population with foreign citizenship registered with the Umbrian Health Care System - An analysis of regional data - Giacchetta, Irene; Primieri, Chiara; Chiavarini, Manuela; De Waure, Chiara; Bietta, Carla (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Non-italian citizens experienced less access to anti-COVID-19 vaccination, compared to the native population. Literature has found differences in adherence to anti-COVID-19 vaccination among these groups; however, there are apparently no studies that investigated the role of citizenship. Our objective was to investigate the role of citizenship in vaccine hesitancy toward anti-COVID-19 vaccination and the completion of vaccine cycle, in the non-Italian citizens resident in the Umbria Region. Study design. This is a population study, performed on resident population in Umbria. Methods. Population data were obtained thanks to a record linkage between the Regional Health Information System and the regional DBCOVID Umbria database. On this dataset, a descriptive and logistic regression analyses were performed. Results. The 19.2% of non-Italian citizens did not take even one dose, 2.1% did not complete it and 40.6% did not take the additional dose. The range of values of which these results are an average, however, is very wide, suggesting important differences in COVID- 19 vaccine up taking, among different citizenships. The logistic regression shows that citizenships with the highest probability of non-adherence to vaccination, compared to Philippine, was Romanian (OR=7.8), followed by Macedonian (OR=7.3) and Polish (OR=5.9). Conclusions. The study provides evidence of differences among citizenships that pinpoint the importance of understanding the reasons behind these behaviours, to support decisions around health policies tailored to each citizenship.